دراسة تشريحية ونسيجية مقارنة للسان بين الخفاش المصري PIPISTRILLUS KUHLI والخفاش السوري PIPSTRILLUS KUHLI - سليم عطيات; إبراهيم نهلة; شلفة مها (Latakia University Journal -Biological Sciences Series, 2019)
The microscopical anatomy of the tongue of the Egyptian Pipistrillus kuhli and the Syrian Pipistrillus kuhli are similar to that of the other mammals but with some specialized structures .In the first specimens the tongue is characterized by the presence of numerous filiform papillae at its dorsal surface, a moderate number of fungiform papillae and a small number of circumvallate . In the second one the circumvallate papillae absent by using bromophenol blue stain to detect the protein content indicate that the protein content of the papillae of the Egyptian bat give more dense reaction than those of Syrian one .Also the same result observed by using Periodiac acid Schiff reaction to detect with carbohydrate content التشريح المجهري, للسان الخفاش المصري Pipistrillus kuhli, والخفاش السوري Pipistrillus , kuhli مشابه لألسنة الثدييات الأخرى، ولكن مع بعض البنى المتخصصة. في العينات الأولى تميز اللسان بوجود حُلَيماتٌ خَيطِيَّة على السطح الظهري، بعدد معتدل منها، وكمية أصغر من الحُلَيماتُ الكَأسِيَّة. وفي العينات الأخرى كانت الحُلَيماتُ الكَأسِيَّة غائبة. وباستخدام صباغ أزرق البروموفينُول تبين أن محتوى البروتين لحليمة الخفاش المصري يعطي تفاعلاً أكثر كثافةً من تلك التي للخفاش السوري. وأيضاً، لوحظت النتيجة نفسها باستخدام تفاعل شيفْ للحَمْضِ البيريوديّ, لكشف محتوى الهيدروكربونات